Blunted nutrient-response pathways in adipose tissue following high fat meals in men with metabolic syndrome: A randomized postprandial transcriptomic study. Issue 3 (March 2021) - Dordevic, Aimee L.; Coort, Susan L.; Evelo, Chris T.; Murgia, Chiara; Sinclair, Andrew J.; Bonham, Maxine P.; Larsen, Amy E.; Gran, Petra; Cameron-Smith, David
Summary: Background: Excessive adipose tissue is central to disease burden posed by the Metabolic Syndrome (MetS). Whilst much is known of the altered transcriptomic regulation of adipose tissue under fasting conditions, little is known of the responses to high-fat meals. Methods: Nineteen middle-aged males (mean ± SD 52.0 ± 4.6 years), consumed two isocaloric high-fat, predominately dairy-based or soy-based, breakfast meals. Abdominal subcutaneous adipose biopsies were collected after overnight fast (0 h) and 4 h following each meal. Global gene expression profiling was performed by microarray (Illumina Human WG-6 v3). Results: In the fasted state, 13 genes were differently expressed between control and MetS adipose tissue (≥1.2 fold-difference, p  < 0.05). In response to the meals, the control participants had widespread increases in genes related to cellular nutrient responses (≥1.2 fold-change, p  < 0.05; 2444 & 2367 genes; dairy & soy, respectively). There was blunted response in the MetS group (≥1.2 fold-change, p  < 0.05; 332 & 336 genes; dairy & soy, respectively). Conclusions: In middle-aged males with MetS, a widespread suppression of the subcutaneous adipose tissue nutrient responsive gene expression suggests an inflexibility in the transcriptomic responsiveness to both high-fat meals.